1)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/8
Пошаговое объяснение:
1 > 10/81)5/6 > 2/3
3,7
(15а – 8а + 7 – 5а) ∙0,5 = 7,5a - 4a + 3,5 - 2,5a = a + 3,5
при а = 0,2
a + 3,5 = 0,2 + 3,5 = 3,7
1)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/8
Пошаговое объяснение:
1)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/81)5/6 > 2/3
1 > 7/8
2/9 > 1/6
1 > 10/8
3,7
Пошаговое объяснение:
(15а – 8а + 7 – 5а) ∙0,5 = 7,5a - 4a + 3,5 - 2,5a = a + 3,5
при а = 0,2
a + 3,5 = 0,2 + 3,5 = 3,7